Diabetes Is Negatively Associated With Meeting Physical Activity Time-Intensity Guidelines in Patients With Claudication. Issue 2 (16th March 2023) - Gardner, Andrew W.; Montgomery, Polly S.; Zhang, Shangming; Pomilla, William A.; Wang, Ming; Shen, Biyi; Liang, Menglu
Abstract : Thirty-one percent of patients with claudication met the physical activity (PA) time-intensity guidelines. Patients with diabetes were least likely to meet the PA time-intensity guidelines, as they had a 69% lower chance than patients without diabetes. Patients who have diabetes should be encouraged to increase their daily PA. Abstract : Purposes: We determined the percentage of patients with peripheral artery disease (PAD) and claudication who meet the 2018 physical activity (PA) time-intensity guidelines, and we identified the clinical characteristics associated with the status of meeting the guidelines. Methods: Five hundred seventy-two patients were assessed on their daily ambulatory activity for 1 wk with a step activity monitor, and were evaluated on whether or not they achieved 150 min/wk of moderate-intensity PA. Results: Thirty-one percent (n = 175) of the patients with PAD met the PA time-intensity guidelines and 69% (n = 397) did not. In a final multivariable logistic regression model identifying the independent predictors of meeting the PA time-intensity guidelines from clinical characteristics, diabetes was the only significant variable entered (OR = 0.310: 95% CI, 0.175-0.538; P < .001) and was associated with a 69% lower chance of meeting the guidelines. Patients with diabetes spent less daily time in moderate-intensity ambulatory PA than patients without diabetes (15 ± 13 vs 23 ± 20 min/d; P < .001). Conclusions: Thirty-one percent of patients with PAD and claudication met the PA time-intensity guidelines. Furthermore, patients with diabetes were least likely to meet the PA time-intensity guidelines, as they had a 69% lower chance than patients without diabetes. The clinical significance is that PAD patients who have diabetes are particularly susceptible to being physically sedentary, and are therefore prime patients who should be encouraged to increase their daily PA.